(untitled) (Herald of the National Children’s Medical Center, 2024)
This article will discuss the prevention of vitamin D deficiency in children. Vitamin D is part of the group of fat-soluble vitamins and is involved in the absorption of calcium and phosphorus, which are necessary for the strength of bones and teeth in children and adolescents. Vitamin D also supports the immune system, helping the body fight infections and inflammation. Prevention of vitamin D deficiency is becoming relevant today.